Analysis of Archery Performance Development at the Kuningan Regency Archery Association - Enda Sukenda; Dedi Iskandar (Journal of Social Research, 2026)
Archery is a sport of achievement that is relatively new to the people of Kuningan Regency. The people of Kuningan are more familiar with traditional archery, which involves shooting arrows from a sitting position and is displayed annually during the anniversary of Kuningan Regency. Perpani Kuningan Regency has excellent achievements and can compete with other sports. The objective of this research is to describe the coaching of archery sports achievements. This study employs a qualitative descriptive research design using three components: data reduction, data presentation, and drawing conclusions. The research was conducted in Kuningan Regency. The study subjects included the branch administrator, coaches, athletes, and KONI. Data were collected using the data triangulation method. The instruments used were observation, interviews, and document analysis. The results of this study indicate that the coaching implemented by PERPANI Kuningan Regency follows the coaching pyramid model as well as general coaching practices. This is evident from the structured development pathway, which includes the selection of novice athletes, junior athletes, and senior athletes. In addition, athlete nurseries continue through extracurricular activities in several schools and archery clubs in Kuningan Regency. The infrastructure owned by PERPANI Kuningan Regency is very adequate; it includes equipment as well as a dedicated outdoor practice field.